Prospective Audit to Study urokinaSe use to restore Patency in Occluded centRal venous caTheters (PASSPORT 1). Issue 6 (November 2019) - Kumwenda, Mick John; Mitra, Sandip; Khawaja, Aurangzaib; Inston, Nicholas; Nightingale, Peter
Objectives: Tunnelled central venous catheters dysfunction can be defined as failure to provide blood flow above 200 mL/min during dialysis often caused by thrombosis. Although urokinase is used routinely for thrombolysis, there is wide variation in dose regimens. A multidisciplinary group was formed to address this issue and offer guidance. Methods: Dialysis centres that used urokinase in the United Kingdom took part in a prospective study to determine the safety and outcomes of thrombolysis using agreed protocols. Data were collected anonymously from September 2017 until February 2018. Catheter blood flow was measured before and after the following interventions: catheter dwell or push locks with 12, 500–50, 000 IU or catheter infusion with 100, 000–250, 000 IU of urokinase. Interventions were repeated if the blood flow remained below 200 mL/min. Results: 10 centres took part and recruited 200 patients; 45.5% were female and 54.5% were male with mean age of 63.6 (±15.2) years. The cumulative success rate for thrombolysis was 90.5% after first intervention, 97% after second intervention, and 99% after more than 2 interventions. Although there was trend towards benefit with dose increments, the success rate between push/dwell locks and high-dose infusion of urokinase was not significantly different (p = 0.069). Seventeen (8.5%) tunnelled central venous catheters were removed due to failure of treatment. No urokinase-related adverse events were reported. Conclusion: In this study, urokinase was safe and efficacious; there was no difference between dwell and push locks. There was some benefit with high-dose infusion of urokinase compared to the dwell and push lock.